Disabled Everyday Life in the Context of the Concept of Social Labeling - Iwona Banach (Maria Curie-Skłodowska University, Lublin, Poland, 2021)
Summary: Introduction The article deals with issues related to the perception and positioning of people with disabilities in the current space of social life. It was pointed out that the conditions and possibilities of everyday human existence and access to everyday spaces, regardless of the level of fitness, constitute an opportunity to normalize interpersonal relations based on a democratic order. Evidence-based Facts It shows the changes that have taken place in the last fifty years in terms of changing attitudes towards people with disabilities, it can be described as a definite departure from the current cultural tradition. Sociological theories may prove useful for the analysis of the social situation and attitudes adopted by society towards people with disabilities. Therefore, in the further part of the article an attempt was made to analyze and explain the situation and the perception of people with disabilities, looking for justification in the theory of social marking. This theory assumes that the main difficulty in the functioning of people with disabilities is the imposition of predetermined behavior in various everyday situations by a healthy and efficient part of society. The concept of social marking, adopting the social model of disability, thus defining it as a restriction in fulfilling social roles. Summary The content of the material refers to everyday life considered as the area of social reality closest to man, which he tries to explain in the course of his family life, relationships and relationships with other people, professional work and participation in culture. To explain the attitudes adopted towards people with disabilities, the cited theory of social marking may be used, which allows for a deeper consideration and penetration into the essence of an interesting phenomenon.